Distinct Epithelial Cell Profiles in Normal Versus Induced-Congenital Diaphragmatic Hernia Fetal Lungs - Gonçalves, Ana N.; Correia-Pinto, Jorge; Nogueira-Silva, Cristina (Frontiers in Pediatrics, 2022)
Background: Recent studies identified a great diversity of cell types in precise number and position to create the architectural features of the lung that ventilation and respiration at birth depend on. With damaged respiratory function at birth, congenital diaphragmatic hernia (CDH) is the more severe cause of fetal lung hypoplasia with unspecified cellular dynamics. Objectives: To characterize the epithelial cell tissue in hypoplastic lungs, a careful analysis regarding pulmonary morphology and epithelial cell profile was conducted from pseudoglandular-to-saccular phases in normal versus nitrofen-induced CDH rat lungs. Design: Our analysis comprises the whole lung by quantification of the relative expression levels (western blot) and the specific pulmonary structures that were evaluated in terms of spatiotemporal distribution (immunohistochemistry). Surfactant protein-C (SP-C), calcitonin gene-related peptide (CGRP), clara cell secretory protein (CCSP), and forkhead box J1 (FOXJ1) were the used molecular markers for alveolar type II, pulmonary neuroendocrine, clara, and ciliated cell profiles, respectively. Results: Generally, we identified an aberrant expression of SP-C, CGRP, CCSP, and FOXJ1 in induced-CDH lungs. For instance, the overexpression of FOXJ1 and CGRP in primordia of bronchiole defined the pseudoglandular stage, whereas the increased expression of CGRP in bronchi; FOXJ1 and CGRP in terminal bronchiole; and CCSP and SP-C in BADJ classified the canalicular and saccular hypoplastic stages. Our findings also describe unexpected FOXJ1 positive cells in BADJ at canalicular and saccular stages, whereas the multi cilia observed in bronchi were notably absent at embryonic day 21.5 in nitrofen-induced CDH lungs. Conclusion: The recognized alterations in the epithelial cell profile contribute to a better understanding of neonatal respiratory insufficiency in induced-CDH lungs and indicate a problem in the epithelial cell differentiation in hypoplastic lungs.